Answer:
<u><em>Yes.</em></u>
Step-by-step explanation:
<em>To find the answer we will put it into the equation, since</em><em><u> x = 1 and y = 2</u></em><em> we will write it like this, </em><u><em>6(1) - 2 > 3.</em></u><em> Since </em><u><em>6 x 1 = 6</em></u><em>, we will now </em><u><em>subtract 6 from 2 which equals 4</em></u><em>. Therefore, the equation is </em><u><em>correct because 4 is bigger than 3.</em></u>
If (y-1) is a factor of f(y), f(y)=0 when y=1. So if you find that f(1)=0, then (y-1) is a factor of f(y).
f(y)=y^3-9y^2+10y+5
f(1)=1-9+10+5=7
Since f(1)=7, (y-1) is not a factor.
The value is -8 of the expression
Answer:
39.55
Step-by-step explanation:
24.99+15=39.55
That is how you get your answer :)
12 x 3 = 36
48 - 36 = 12
The 4th side is also 12 feet.